Distinct requirements for C.elegans TAF(II)s in early embryonic transcription - Walker, Amy K. (Oxford University Press, 2001)
TAF(II)s are conserved components of the TFIID, TFTC and SAGA-related mRNA transcription complexes. In yeast (y), yTAF(II)17 is required broadly for transcription, but various other TAF(II)s appear to have more specialized functions. It is important to determine how TAF(II)s contribute to transcription in metazoans, which have larger and more diverse genomes. We have examined TAF(II) functions in early Caenorhabditis elegans embryos, which can survive without transcription for several cell generations. We show that taf-10 (yTAF(II)17) and taf-11 (yTAF(II)25) are required for a significant fraction of transcription, but apparently are not needed for expression of multiple developmental and other metazoan-specific genes. In contrast, taf-5 (yTAF(II)48; human TAF(II)130) seems to be required for essentially all early embryonic mRNA transcription. We conclude that TAF-10 and TAF-11 have modular functions in metazoans, and can be bypassed at many metazoan-specific genes. The broad involvement of TAF-5 in mRNA transcription in vivo suggests a requirement for either TFIID or a TFTC-like complex.